2019
DOI: 10.3389/fmicb.2019.00899
|View full text |Cite
|
Sign up to set email alerts
|

Strategies Developed by Toxoplasma gondii to Survive in the Host

Abstract: One of the most successful intracellular parasites, Toxoplasma gondii has developed several strategies to avoid destruction by the host. These include approaches such as rapid and efficient cell invasion to avoid phagocytic engulfment, negative regulation of the canonical CD40-CD40L-mediated autophagy pathway, impairment of the noncanonical IFN-γ-dependent autophagy pathway, and modulation of host cell survival and death to obtain lifelong parasite survival. Different virulent strains ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 129 publications
0
27
1
14
Order By: Relevance
“…Consistent with the previous finding reported in T. gondii-infected mouse liver (He et al, 2016a), many IRGs and GBPs-related genes were upregulated. Although increased expression of IDO in the brain as antitoxoplasma mechanism to control the parasite replication has been reported in previous studies (Nagineni et al, 1996;Zhu et al, 2019), the expression level of IDO did not change in response to T. gondii infection in this study.…”
Section: Discussioncontrasting
confidence: 72%
“…Consistent with the previous finding reported in T. gondii-infected mouse liver (He et al, 2016a), many IRGs and GBPs-related genes were upregulated. Although increased expression of IDO in the brain as antitoxoplasma mechanism to control the parasite replication has been reported in previous studies (Nagineni et al, 1996;Zhu et al, 2019), the expression level of IDO did not change in response to T. gondii infection in this study.…”
Section: Discussioncontrasting
confidence: 72%
“…Previous studies demonstrated that autophagy contributes to host immune defenses against T. gondii infection [8,18]; however, the role of 4-HBA in autophagy activation has not been characterized. To determine whether 4-HBA treatment We next attempted to investigate the role of autophagy in 4-HBA-mediated anti-toxoplasma activity.…”
Section: -Hba-induced Autophagy Played An Essential Role In the Actimentioning
confidence: 98%
“…T. gondii can actively invade and replicate in all nucleated cells, particularly in the brain and retina. 17 It has developed several strategies, such as resistance to oxidative stress and modulation of host cell survival and death to obtain lifelong parasite survival, to avoid destruction by internal and external stimuli. 17,18 Several studies have shown that cells infected with T. gondii are resistant to multiple inducers of apoptosis, including Fas-dependent and Fas-independent CTL-mediated cytotoxicity, IL-2 deprivation, irradiation, UV irradiation, the calcium ionophore beauvericin, and actinomycin D, staurosporine, exogenous cytochrome c and dATP.…”
Section: Introductionmentioning
confidence: 99%
“…17 It has developed several strategies, such as resistance to oxidative stress and modulation of host cell survival and death to obtain lifelong parasite survival, to avoid destruction by internal and external stimuli. 17,18 Several studies have shown that cells infected with T. gondii are resistant to multiple inducers of apoptosis, including Fas-dependent and Fas-independent CTL-mediated cytotoxicity, IL-2 deprivation, irradiation, UV irradiation, the calcium ionophore beauvericin, and actinomycin D, staurosporine, exogenous cytochrome c and dATP. [19][20][21][22][23] T. gondii inhibits staurosporine-or exogenous cytochrome c/dATPinduced mitochondrial apoptosis by preventing the release of cytochrome c and phosphorylation of the pro-apoptotic Bad protein and inducing overproduction of the anti-apoptotic protein Bcl-2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation